MODERASI BERAGAMA MENURUT YUSUF Al-QARDHAWI, QURAISH SHIHAB, DAN SALMAN AL-FARISI - Khalida An Nadhrah, Nabila; Casram; Hernawan, Wawan (Living Islam: Journal of Islamic Discourses, 2023)
Abstract This study describes the concept of religious moderation according to Yusuf Al-Qardhawi, Quraish Shihab, and Salman al-Farisi. This research is caused by the current reality that religious moderation is considered a new understanding in Islam, even though religious moderation has existed since the time of the Prophet Muhammad SAW. So this is first step to examine the concept of religious moderation. The type of research used is qualitative with method of library research (library research) through the stages of observation, and library documentation. The results and discussion of this study is that the Prophet Muhammad SAW., has taught the concept of religious moderation through the Koran and his Sunnah. The results of this study indicate that both Yusuf Al-Qardhawi, Quraish Shihab, and Salman al-Farisi agree that: first, religious moderation mediates between religious understandings without losing track of the ash-shalah. Second, religious moderation can mediate differences in understanding of religion, avoiding the occurrence of radicalism and excessive fanaticism in religion for adherents. This research is important as a basic reference in practicing the essence of religious teachings which place more emphasis on human values and spreading the common good. Keywords: Religious Moderation, Yusuf al-Qardhawi, Quraish Shihab, Salman Al-Farisi   Abstrak Penelitian ini menjabarkan tentang konsep moderasi beragama menurut Yusuf Al-Qardhawi, Quraish Shihab, dan Salman al-Farisi. Penelitian ini disebabkan oleh realitas yang ada saat ini moderasi beragama justru dianggap sebagai paham baru dalam Islam, padahal moderasi beragama sudah ada sejak zaman Nabi Muhammad SAW. Maka hal tersebut menjadi langkah awal untuk mengkaji konsep moderasi beragama. Jenis penelitian yang digunakan adalah kualitatif dengan metode studi pustaka (library research) melalui tahapan observasi, dan dokumentasi pustaka. Hasil dan pembahasan penelitian ini adalah Nabi Muhammad SAW., sudah mengajarkan konsep moderasi beragama melalui Alquran dan Sunnah-nya. Hasil penelitian ini menunjukkan, baik Yusuf Al-Qardhawi, Quraish Shihab, maupun Salman al-Farisi sepaham, bahwa: pertama, moderasi beragama menjadi penengah di antara pemahaman keagamaan tanpa kehilangan jejak ash-shalahnya. Kedua, moderasi beragama dapat menengahi perbedaan pemahaman dalam beragama, menghindari terjadinya radikalisme dan fanatisme berlebihan dalam beragama bagi penganutnya. Penelitian ini menjadi penting sebagai rujukan dasar dalam mengamalkan esensi ajaran agama yang lebih menekankan nilai-nilai kemanusiaan dan menebarkan kebaikan bersama. Kata kunci: Moderasi Beragama, Yusuf al-Qardhawi, Quraish Shihab, Salman Al-Farisi